DAMPAK TUMBUHAN GELAM (Melaleuca cajuputi Powell) TERHADAP STRUKTUR DAN KOMPOSISI VEGETASI LAHAN GAMBUT (STUDI KASUS TERHADAP 4 LAHAN GAMBUT DI KABUPATEN BANJAR KALIMANTAN SELATAN) - Dharmono Dharmono (Universitas Lambung Mangkurat, 2007)
Gelam (Melaleuca cajuputi Powell) has been used in peat land reclamation since 1970. The present study aimed to examine the impact of the gelam revegetation on the structure and composition of vegetation on peat lands. Vegetation analyses were performed on 4 peat lands differed in vegetation. Quadrat method was applied in the systematic sampling. The results showed insignificant difference among peat lands in structure and composition of vegetation. However, some plant species found in non-gelam covered peat lands were not recovered in gelam-covered peat lands: Adina minutiflora (Rubiaceae), Diosphyros perfida (Ebenaceae), Shorea compressa (Dipterocarpaceae), dan Baccaurea bracteata (Euphorbiaceae).